Unusual encounters in a hernia sac - Vagholkar, Ketan; Pawanarkar, Amish; Vagholkar, Suvarna; Iyengar, Madhavan; Pathan, Kashmoorvalishah (International Journal of Research in Medical Sciences, 2016)
Contents of a hernia sac are always a surprise. In most cases the contents of the sac determine the type of repair. A case of an inguinal hernia sac containing the appendix along with the dislodged end of a ventriculoperitoneal shunt tube is presented in view of its rarity.